Influence of School Climate on Teachers’ Turnover Intention in Public and Private Primary Schools, Ikeja City, Lagos, Nigeria - Ittai, Joy; Ogunji, James (European Scientific Journal, ESJ, 2025)
Teacher career turnover is a serious global occupational hazard, with the estimated teacher turnover rate ranging from 13 to 15% annually. Even countries with the best educational systems are not insulated in this regard. There cannot be actual turnover without turnover intentions, which are a key precursor. Being a multilevel structured phenomenon, several school variables could be implicated, such as school climate and job satisfaction. The Nigerian education system is portrayed as an environment where turnover intention thrives. Due to the dearth of literature on this regard in Lagos state, Nigeria, this research work utilized a survey research design to study the phenomenon in public and private primary schools. A total of 373 teachers were sampled using a simple random technique, and data was collected through a structured questionnaire. Appropriate descriptive and inferential statistics, such as Pearson product moment correlations, simple linear regression, and Independent t-tests, were used to analyze the data. The findings revealed that there was a moderate negative significant influence of school climate of public and private primary schools’ teachers on turnover intention. This means as school climate improves, the turnover intention goes down. School climate measures (safety, academic climate, community climate and organizational environment) jointly influenced teachers’ thinking of quitting their current job. There was a significant difference between public and private primary schools’ teachers’ turnover intentions. The study concluded that school type (public or private primary schools’ climate) has a significant, moderating effect on teachers’ turnover intention. Teachers’ turnover intention was higher in private schools. It is recommended that public and private primary schools in Ikeja City should intentionally improve school climate by improving safety, academic climate, community climate, and organizational environment to reduce teacher turnover intention.